Evaluation of the effect of red guava (Psidium guajava) fruit extract on tyrosinase (EC 1.14.18.1) activity by spectrophotometry - Puspaningtyas, Ayik Rosita (International Current Pharmaceutical Journal, 2012)
Tyrosinase is one of the most important enzymes in melanin biosynthesis. Inhibition of tyrosinase activity will cause a decrease in melanin production. Tyrosinase inhibitory activity by ascorbic acid has been studied before. Based on reported experiments, ascorbic acid can inhibit tyrosinase activity in enzymatic reaction competitively. As an effort to find out a skin whitening agent which is effective, safe and have minimum adverse effect, the inhibitory activities of Psidium guajava extract was studied on tyrosinase activity. This is one of the fruits that contains high amount of ascorbic acid. To determine the efficacy of tyrosinase inhibition, L-tyrosine was used as the substrate, P. guajava ex-tract as inhibitor and ascorbic acid as positive control that was measured by spectrophotometry. The optimization of method was also performed. The inhibitory kinetics was determined by measuring the absorbance of dopachrome as the end product of the tyrosinase reaction. Michaelis-Menten constant (Km) and maximum velocity (Vmax) of the ty-rosinase were determined by Lineweaver-Burks plots. The Km and Vmax without the fruit extract were 0.315mM and 0.0265?mol/min. The Km value with the fruit extract of 1%, 2% & 3% w/v were 0.4824, 0.698 & 0.543mM, while the Vmax value were 0.0269, 0.0283 & 0.0255 ?mol/min, respectively. Lineweaver-Burks plots in presence of P. guajava fruit extract showed that the extract inhibited tyrosinase competitively. From the plots, the IC50 of the fruit extract was determined as 0.26mM; the control in 0.26mM concentration inhibited 56.523%. Finally, P. guajava fruit extract showed higher effect than ascorbic acid on Tyrosinase activity. DOI: http://dx.doi.org/10.3329/icpj.v1i5.10280 International Current Pharmaceutical Journal 2012, 1(5): 92-97